CONTINUITY OF MIDWIFERY CARE FOR MRS. T WITH BREAST ENGORGEMENT AT YUNAJI SRI REZEKI INDEPENDENT MIDWIFERY PRACTICE, MEDAN TEMBUNG DISTRICT, DELI SERDANG REGENCY NORTH SUMATRA, YEAR 2025 - Afni Yuliani; Sinaga, Rosmani; Yunaji Sri Rejeki; Abel Amanda; Gulo, Fransiska; Daryani; Asi Esterina Sarumpaet, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (AKB) are important indicators in describing the welfare of a country's society. The high number of maternal deaths during pregnancy, childbirth, and postpartum periods, including those caused by accidents or falls, shows a major problem in Indonesia in this regard. Development in the health sector focuses on improving community welfare. The Sustainable Development Goals (SDGs) continue the Millennium Development Goals (MDGs) agenda through 2030, to follow up on the MDGs and achieve 169 targets by 2023 (Ministry of Health of the Republic of Indonesia, 2021). The results of a survey conducted among PMB midwives in December-February 2024/2025 indicate that 60 maternity mothers were recorded. In December-February 2024/2025, 20 postpartum mothers visited the Yunaji Midwife Clinic for postpartum follow-up. During the visit, there were 10 postpartum mothers; one of them was 1 experiencing breast milk dams due to breastfeeding that was not continuously, the baby has not breastfed properly, the breastfeeding position is not correct, abnormalities in the nipples, the use of BH is too tight, and during pregnancy the mother does not do breast care or the mother's lack of knowledge about breast care From the results of the research survey obtained from 10 postpartum mothers, including 1 postpartum mother who experienced a breast milk dam, so the author carried out midwifery care for Mrs. T at the age of 38 years postpartum 6 days ago P4A0 with a breast dam. The purpose of the care is to anticipate complications in the mother and baby, as well as problems that can be addressed through breast care for Mrs. T at PMB Yunaji, Kec.Medan Tembung Regency, Deli Serdang, North Sumatra 2024.